Effects of longitudinal whole-body electromyostimulation on muscular power and endurance parameters in sportspeople and athletes - Püschel, M.; Kohl, M.; von Stengel, S.; Shojaa, M.; Filipovic, A.; Kemmler, W (Deutsche Zeitschrift für Sportmedizin, 2026)
Summary